METHODS OF EVALUATION OF PERFORMANCE PROFESSIONAL FOOTBALL USED BY QUALIFIED (Fiep Bulletin - online, 2011)
A major concern in the sports area is to identify and select talent in football. For this sport generates direct or indirect resources for players, clubs, media, sports brands and their sponsors. It is also known that the professional clubs, daily, arriving several players to try to be a professional soccer player, however, most clubs do not present a methodological point, systematic and analytical framework for selecting promising players. The selection processes ( "frills" or "peneirões") developed by technical observers (scouts) are summarized in the observation of the sports performance of a large group of players in a period of several minutes given to each player. And if they are identified promising players in this squad, they are referred to the club for a new observation, which will be conducted by the official category in question. However, the absence of common criteria and performance indicators between these professionals can hinder the evaluation of players as well as be a costly activity for the club. This study proposes to identify and characterize the assessment methods used by staff of the academy of Andhra Pradesh to assess the sporting performance of young players, in order to compare these methods of evaluation used by technicians with different times of experience. The study contained 46 categories of technical base of the RN. And by analyzing the results in relation to methods for evaluating athletic performance used by technicians, it was noted that most clearly use observation only to select young footballers. Therefore, it is noted that there must be a systematic selection of players, as there is complexity in the verification of aspects and characteristics involved, so you can avoid wrong evaluations and selections and weak results.
Keywords: football; evaluation; performance sports